Similar outcome with a new anteverted or a straight standard stem: a randomized study of 72 total hip arthroplasties evaluated with clinical variables, radiostereometry, and DXA up to 2 years - Karin Rilby; Maziar Mohaddes; Emma Nauclér; Johan Kärrholm (Acta Orthopaedica, 2022)
Background and purpose — The anatomical uncemented stem, SP-CL (Static Physiologicus – CementLess), designed to facilitate insertion and to avoid stress concentration at solitary contact points, has been on the market since 2014 but is not well documented. We studied its clinical performance, migration, and associated bone remodeling in a randomized controlled trial, with the Corail stem as control.